Modeling of Maximum Power Point Tracking Controller for Solar Power System - Aryuanto Soetedjo; Abraham Lomi; Yusuf Ismail Nakhoda; Awan Uji Krismanto (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
In this paper, a Maximum Power Point Tracking (MPPT) controller for solar power system is modeled using MATLAB Simulink. The model consists of PV module, buck converter, and MPPT controller. The contribution of the work is in the modeling of buck converter using equation model approach rather than circuit model one.  The buck converter model is developed using equation model that allowing the input voltage of the converter, i.e. output voltage of PV is changed by varying the duty cycle, so that the maximum power point could be tracked when the environmental changes. From the experiment, the developed model comforms with the circuit model provided by MATLAB Simulink Power Simulation. Furher, the simulation results show that the developed model performs well in tracking the maximum power point (MPP) of the PV module using Perturb and Observe (P&O) Algorithm.